The centrality of Christology: On the relation between Nicholas Cusanus and Martin Luther. (2nd January 2016) - Alfsvåg, Knut
Abstract : Martin Luther seemingly never read the works of Nicholas Cusanus; still, scholars have found the relationship between the two to be an intriguing one. In this essay, it is argued that this relationship is best explored as a common emphasis both on divine unknowability and on the significance of Christology, and that this common emphasis is closely related to the importance they both attached to the works of Plato and Dionysius at important points in their careers. Given this common framework, it comes as no wonder that they both found the Pauline gospel of justification through faith and Chalcedonian two-nature Christology indispensable both philosophically and theologically. In this way, they represent a renewal of central aspects of the theology of the Church Fathers that today seem both theologically attractive and ecumenically relevant.